IMPACT SCORE TECHNIQUE AND SERVQUAL COMPARISON FOR PUBLIC TRANSPORTATION SERVICE QUALITY - Akyildiz Alcura, Guzin; Kusakci Gundogar, S. Seyma; Tanriverdi, Cankat; Golbasi Simsek, Gulhayat; Gursoy, Mustafa (YILDIZ TECHNICAL UNIV, 2020)
Determination of service quality measures that have the greatest impact on overall satisfaction of a system has many advantages both in favor of passengers and managers. Service quality of a transportation system mostly found by evaluation of passengers attitudes. Especially for managers, it is very important to have knowledge about the expectations and perceptions of passengers that they provide service. In this study, two well-known methods, Servqual and Impact Score Technique (IST) are used to determine the service quality of High Speed Rail System of Turkey operated between Eskisehir and Ankara. Then, the results were compared and an analysis was conducted focusing on the differences that have arisen because of the approaches of the methods. The data collected from 900 passengers of High Speed Rail System (HSRS) were used in the analysis. For Servqual, the expectations and perceptions of passengers were taken into account, while in IST, the ratio of passengers having experienced a problem about the relevant attribute and their perceptions are used. The results show that in IST, the outstanding problematic areas are ranked according to problem experiencing rates; while in Servqual, ranking is mostly shaped by perceptions of passengers. In both methods, the featuring attributes of the system are found to be almost common.
Keywords: Service quality; public transportation; impact score technique; servqual; CONSUMER PERCEPTIONS; PASSENGERS; SATISFACTION; Engineering